Pengaruh Atribut Kemasan Terhadap Minat Beli Konsumen(Studi Empiris Pada Konsumen Mie ABC Cup Di Kota Surakarta) - Larissa, Elian Alvaroy; , Drs. Wiyadi, MM (2016)
This study aims to examine the influence of the attributes of color, shape, material, design and size of product packaging ABC Noodle Cup on consumer buying interest. The sample in this study is partly Surakarta city residents who never consume or buy products ABC Cup Noodle. Total sample of 100 respondents to the survey method, the process of collecting data by distributing questionnaires to the respondents. sampling technique with nonrandom sampling that by using purposive sampling. Analysis technique used in this research is multiple linear regression analysis. The results of data analysis and hypothesis testing showed that the attributes of color, shape, material, design, and packaging sizes significantly influence consumers to buy. Researchers next need to add another variable, such as brand, price, product quality and so forth in order to provide more accurate results. Keywords: attributes of color, shape attributes, attributes of material, design attributes, attributes the size of packaging, buying interest.